Intralipid infusion therapy as an adjunct treatment in women experiencing adenomyosis-related infertility - James Henshaw; Kelton Tremellen (SAGE Publishing, 2023)
Background: Currently, there is some evidence that adenomyosis patients using gonadotropin-releasing hormone (GnRH) agonist long downregulation (LDR) prior to embryo transfer may improve in vitro fertilization (IVF) success rate, but not to the baseline expected success where there is no adenomyosis. Given the association between adenomyosis and an aberrant endometrial immune environment, many physicians also use prednisolone or Intralipid adjuvant treatments in combination with GnRH agonist therapy, despite neither being of proven benefit. Objective: The purpose of this study was to investigate whether the addition of prednisolone or Intralipid immune therapy to GnRH agonist LDR improves fertility outcomes in patients with adenomyosis. Methods: This is a retrospective cohort study of 116 consecutive adenomyosis patients who underwent their first transfer of a genetically screened euploid embryo between January 2019 and December 2020 at a private IVF clinic. Results: There was no difference in maternal age, body mass index, number of embryo's transferred and gravidity or parity among the three treatment groups. Patients who received Intralipid had a poorer prognosis with a longer duration of infertility (4 years) and a higher number of previous embryo transfers (ETs, 5 previous ETs) compared to the comparison groups. Logistic regression analysis adjustment for all covariates revealed that LDR plus Intralipid therapy produced significantly higher live birth rates (LBRs; 60%) compared to LDR alone (40% LBR); yet, the addition of prednisolone to GnRH agonist LDR (30% LBR) provided no additional live birth benefit. Conclusion: In this retrospective analysis, we showed Intralipid adjuvant treatment in combination with GnRH agonist therapy in adenomyosis patients undergoing IVF resulted in a LBR expected in women without adenomyosis using preimplantation genetic testing screened embryos. This benefit was not seen when using prednisolone as an adjuvant to GnRH agonist LDR. Future randomized clinical trials will be required to confirm the therapeutic benefit of Intralipid in combination with GnRH agonist therapy.